Reestablishment of public stale libraries in the postwar Lithuania - Sinkevičius, Klemensas (Knygotyra, 1988)
Before the Hitler occupation in Soviet Lithuania, there were no less than 263 working public state libraries, and preparations for the establishment of 92 additional libraries were underway. After the liberation of Soviet Lithuania, 60 libraries remained, nearly destroyed. Reconstruction and establishment work were carried out in three directions: reconstructing libraries that had been destroyed by the Hitler occupation forces, establishing libraries that had been planned before the war, and building new ones that had not been planned earlier. By the end of 1949, all the prewar libraries and those planned to be built had been reestablished and founded, except for 19, the construction of which was postponed for a later time. Additionally, more than 70 new state public libraries were founded.
Keywords: -